Kajian Hidrologi dan Potensi Dekarbonisasi Pada Pembangkit Listrik Tenaga Air Run Off River Batang Toru Kabupaten Tapanuli Selatan (Jurnal Riset Teknik Sipil dan Sains, 2025)
Indonesia has significant water resources potential for the development of hydropower plants, including the Batang Toru River with a power potential of 510 MW that has not yet been fully utilized. This study aims to analyze the hydrological potential of the Batang Toru River, calculate the potential electricity generation capacity, and evaluate the potential reduction of carbon emissions to support sustainable and environmentally friendly hydropower operations. The research methods include literature review, collection of historical rainfall and river discharge data, hydrological analysis to determine reliable discharge, hydraulic analysis to calculate the effective head, and simulation of the potential power generation capacity. The results show that the 90% reliable discharge (Q90) of 72.67 m³/s is insufficient to meet the 510 MW power demand, thus requiring the construction of a reservoir with a design discharge of 219.494 m³/s. With this discharge, the Batang Toru Hydropower Plant can generate 510 MW of electricity and is estimated to reduce carbon emissions by 1,326,645 tons per year. This study recommends expanding hydrological data coverage, utilizing GIS-based modeling technology, and conducting economic feasibility and environmental impact analyses to improve the efficiency and sustainability of the hydropower plant